El Patrimonio Histórico Arquitectónico de la ciudadela Bellavista y el impacto en la identidad cultural de sus habitantes, durante el periodo 2013 - 2014 - Cortez Vega, Eduardo Patricio (2016)
This investigation concerns the Architectural Heritage of Bellavista Citadel, same that has built inherited from the past assets, these assets have a priceless cultural and aesthetic value so it is necessary to protect the buildings that we have inherited from previous generations and so maintain the collective memory of its people in a way that allows us to preserve the identity of them alive. Unfortunately the inhabitants of the Citadel do not value the architectural heritage aspect that affects their identity. In research emphasize the Historical, Cultural, Material Heritage, with the importance of the Cultural Foundations, Anthropology and Sociology as they are issues of importance to the same. In the Bellavista Citadel once observed the impact of Historical Heritage loss of identity of the people, for the analysis and interpretation identified the Inductively and Historical Method so that part was used from the observation of phenomena or facts of reality to the universal law that contains them, for the collection of information were applied sheets observation ,surveys and interview the same were used in the inhabitants of the village where we expressed the given problems with this context it could be detected that the identity of the inhabitants of the Bellavista Citadel is breaking down with the time, with these results we proceeded to test the hypothesis in the research. Finally it is concluded that it should be preserved the heritage resource valuing and rescuing its local memory and to solve this problem was made an architectural historical guide in order to enrich the Legacy Heritage which owns the Bellavista Citadel.